Inferior vena cava reconstruction for leiomyosarcoma of zone I–III requiring complete hepatectomy and bilateral nephrectomy with autotransplantation. Issue 5 (10th September 2015) - Fernandez, Hoylan T.; Kim, Peter T.W.; Anthony, Tiffany L.; Hamman, Baron L.; Goldstein, Robert M.; Testa, Giuliano
<x xml:space="preserve">Abstract</x> The inferior vena cava (IVC) is the most common site of leiomyosarcomas arising from a vascular origin. Leiomyosarcomas of the IVC are categorized by anatomical location. Zone I refers to the infrarenal portion of the IVC, Zone II from the hepatic veins to the renal veins, and Zone III from the right atrium to the hepatic veins. This is a rare presentation of a Zone I–III leiomyosarcoma. Fifty‐two‐years‐old female with a medical history significant only for HTN was admitted to the hospital with bilateral lower extremity edema and dyspnea. Two‐dimensional echo demonstrated a right atrial thrombus, extending into the IVC. On subsequent CT and MRI, a 15 cm mass was noted that began in the right atrium and extended into the IVC, with continuation below the renal veins to above the level of the confluence of the common iliac veins. The patient underwent a complete resection of the mass, replacement of the IVC with Dacron graft, total hepatectomy and bilateral nephrectomy, with liver and kidney autotransplantation. Pathology was consistent with a high grade spindle cell sarcoma of vena cava origin. Patient was readmitted approximately 4 weeks postoperatively to begin adjuvant chemotherapy. This case represents a zone I–III IVC leiomyosarcoma treated with surgical R0 resection. This included a hepatectomy, bilateral nephrectomy, and hepatic and left renal autotransplantation. These complex tumors should be treated with surgical resection, and require a multidisciplinary approach. J. Surg. Oncol. 2015; 112:481–485. © 2015 Wiley Periodicals, Inc.